Tectonic evolution ofthe Kuujjuaq terrene, New Québec Orogen - Perreault, Serge; Hynes, Andrew (Geoscience Canada, 1990)
Summary The Kuujjuaq terrane of the New Québec Orogen may represent a northern extension of the De Pas batholith, which is thought to be the remnant of a lower Proterozoic continental magmatic arc. Collision between the Kuujjuaq terrane and the Labrador Trough to the west produced intense deformation, associated with large-scale, southwest-directed transport. The Kuujjuaq batholith, thought to be a subduction-related granitoidsuite, was emplaced at a late stage in the deformation. Extensive post-tectonic metamorphism involved retrogression of early granulite-facies mineral assemblages. Our interpretation is that the Kuujjuaq terranewas subjected to deep and protracted burial(>40 m.y.). This is consistent with, and most easily explained by, its development within a major continental collision zone such as that between India and Asia.